The Effectiveness of Sport Massage on Blood Lactic Acid Levels Indonesian Kabaddi Athletes - Subekti, Maryoto; Adiatmika, I Putu Gede; Santika, I Gusti Putu Ngurah Adi; Sudarsana, I Putu Agus Budi (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study was to determine the effectiveness of sport massage in reducing blood lactic acid levels of Indonesian Kabaddi athletes . The research design was a randomized pre and post test control group design with a sample of 20 male athletes who were divided into treatment and control groups. The results showed that there was a decrease in blood lactic acid levels from giving sport massage with a decrease in blood lactic acid levels by 4.6 mmol/L or a decrease of 56.8% for the treatment group. This shows that the provision of sports massage is effective to be given to male athletes of Kabaddi Indonesia to reduce blood lactic acid levels in order to restore physical condition to face the competition.